Naturalistic Study On Communication Strategy Used By The Second Semester Students In Speaking Class Of English Education Department Of Muhammadiyah University Of Surakarta - Novitasari, Dewi, Prof. Endang Fauziati,.M.Hum, Aryati Prasetyarini, S.Pd, M.Pd (2016)
This research in general, aims to describe the communication strategies used by the second semester students in Speaking class of Muhammadiyah University of Surakarta. Specifically, it is to describe: (1) the types of communication strategies, (2) the frequency of communication strategy used by the second semester students in speaking class of Muhammadiyah University of Surakarta, (3) the dominant type of communication strategies used by the second semester students of Muhammadiyah University of Surakarta. The data of research contain communication strategies used by second semester students in speaking class of English Education Department of Muhammadiyah University of Surakarta in 2015/2016 academic year. There are three sources of data in this research, namely: event, informant, and document. The writer takes 2 classes of Speaking, with the total 30 students as the subject of the research. The writer uses descriptive qualitative method in analyzing the data. The data are categorized based on Celce-Murcia taxonomy of communication strategies. The result of this study shows that there are 5 types with 9 subtypes of communication strategies, the most dominant types of communication strategies used by second semester students in Speaking class is fillers with 34,48%, and the rarely type of communication strategies used by students is non-linguistic Means and restructuring with 1,15%. The result above implies that teaching communication strategies is needed for students who still have limited knowledge in the target language. To maintain student's communication, communication strategies as a subject in Speaking Class will make the students aware when they communicate with the others. Keywords: Communication Strategies, Speaking.